Taxonomy of Arnica L. subgenus ChamissonisMaguire (Asteraceae)1 - Gruezo, William Sm; Denford, Keith E. (Asia life sciences :the international journal of life sciences.)
"A multi-disciplinary systematic revision of Arnica L. subgenus Chamissonis Maguire was undertaken. Data derived from field and growth room studies, morphology, cytology, pollen viability, flavonoid chemistry and phytogeography support the recognition of 7 taxa in the subgenus, namely: Arnica parryi A. Gray, A. mollis Hook., A. chamissonis Less, A.longifolia D.C. Eaton, A. lanceolata Nutt. subsp. lanceolata, A. lanceolata Nutt. subsp. amplexicaulis (Nutt.) Gruezo, comb. et stat. nov. (Basionym: Arnica amplexicaulis Nutt.) and A. ovata Greene. The circumscription of the subgenus by Maguire (1943) is accepted, but the sectional divisions erected by him are rejected in favor of a more cohesive phylogenetic arrangement. Arnica lanceolata Nutt. subsp. lanceolata, the only member of the subgenus in eastern North America (restricted areas in Gaspe Peninsula, Quebec; New Brunswick, Maine, New Hampshire and northern New York State), is treated as the main geographic subspecies on account of publication northern New York State), is treated as the main geographic subspecies on account of publication priority. Its disjunction from the more widely distributed Arnica lanceolata Nutt. subsp. amplexicaulis (Nutt.) Gruezo is attributed to the pervasive effect of the Wisconsinan glaciation and the survival of populations in regia or nunataks. Arnica ovata Greene, treated by Maguire (1943) as a synonym of A. mollis Hook., is the correct and valid name for plants widely recognized by numerous authors as A. diversifolia Greene. Arnica silvatica Greene, similarly listed as a synonym of A. mollis Hook. by Maguire (1943) is synonymized with A. ovata Greene. Cytological data, augmented by ploidy determination of herbarium material based on pollen stainability, indicate that in subgenus Chamissonis, diploid (amhimictic) populations of each species are presently found only in refugial sites within the glaciated zone, or in unglaciated areas mostly south of the maximum limits of Wisconsinan/Cordillera glaciations. Most populations now occupying formerly glaciated localities are polyploids that reproduce solely via apomixis. Such populations are successful colonizers of disturbed colonizers of disturbed habitats, hence their current widespread distribution range."